THE INTERDEPENDENCE BETWEEN PERCEIVED SELF-EFFICACY AND SELF-ASSESSMENT SKILLS OF ACADEMIC PROGRESS IN STUDENTS - Blândul, Valentin Cosmin; Bradea, Adela (PROBLEMS OF EDUCATION IN THE 21ST CENTURY, 2022)
Self-assessment in the school environment can be defined as the students’ ability to make valuable judgements about their own academic performance, either by reference to the teacher’s educational goals, previous academic results, or the academic performance of other colleagues. The formation of such self-assessment skills is strongly influenced by a number of internal and external psycho-pedagogical factors, including chronological age, motivation for learning, level of cognitive development, perceived self-efficacy, the teacher's teaching style, the social status of the student's family, their group affiliation, etc. Starting from this point, the purpose of the present research was the analysis of the students’ degree of awareness of the role of perceived self-efficacy in the formation of objective didactic self-evaluation skills. The research sample consisted of 108 students, currently attending the Psycho-Pedagogy and Methodology Study Program courses at the University of Oradea and Emanuel University of Oradea, Romania. The research methodology was targeted at requesting these students to self-assess their performance in a subject of the afore-stated study program, respectively administering a scale for measuring personal self-efficacy. The results showed that most of the students tended to either evaluate themselves objectively or under-evaluate themselves, against the backdrop of a high level of perceived self-efficacy, respectively of superior academic performance.